Genotoxicity of doxorubicin in F344 rats by combining the comet assay, flow‐cytometric peripheral blood micronucleus test, and pathway‐focused gene expression profiling. (24th October 2013) - Manjanatha, Mugimane G.; Bishop, Michelle E.; Pearce, Mason G.; Kulkarni, Rohan; Lyn‐Cook, Lascelles E.; Ding, Wei
<x xml:space="preserve">Abstract</x> Doxorubicin (DOX) is an antineoplastic drug effective against many human malignancies. DOX's clinical efficacy is greatly limited because of severe cardiotoxicity. To evaluate if DOX is genotoxic in the heart, 7‐week‐old, male F344 rats were administered intravenously 1, 2, and 3 mg/kg bw DOX at 0, 24, 48, and 69 hr and the Comet assays in heart, liver, kidney, and testis and micronucleus (MN) assay in the peripheral blood (PB) erythrocytes using flow cytometry were conducted. Rats were euthanized at 72 hr and PB was removed for the MN assay and single cells were isolated from multiple tissues for the Comet assays. None of the doses of DOX induced a significant DNA damage in any of the tissues examined by the alkaline Comet assay. Contrastingly, the glycosylase enzymes‐modified Comet assay showed a significant dose dependent increase in the oxidative DNA damage in the cardiac tissue (P ≤ 0.05). In the liver, only the top dose induced significant increase in the oxidative DNA damage (P ≤ 0.05). The histopathology showed no severe cardiotoxicity but non‐neoplastic lesions were present in both untreated and treated samples. A severe toxicity likely occurred in the bone marrow because no viable reticulocytes could be screened for the MN assay. Gene expression profiling of the heart tissues showed a significant alteration in the expression of 11 DNA damage and repair genes. These results suggest that DOX is genotoxic in the heart and the DNA damage may be induced primarily via the production of reactive oxygen species. Environ. Mol. Mutagen. 55:24–34, 2014. © 2013 Wiley Periodicals, Inc.†